Сучасне трактування, склад і особливості формування управлінської звітності підприємства - Куцик, П. О. (Видавництво Львівської політехніки, 2014)
Досліджено підходи вчених до трактування поняття “управлінська звітність” та її призначення. Обґрунтовано доцільність використання запропонованого терміна “внутрішньокорпоративна управлінська звітність”, який відображає як ціль подальшого використання викладеної у ній інформації, так і суб’єктів, чиїх інтересів вона торкається. Розглянуто класифікацію управлінської звітності, що подається вченими в їх дослідженнях. Подано авторську позицію щодо структурування та визначення складу внутрішньокорпоративної управлінської звітності, її місця в системі інформаційного забезпечення системи управління. Reveals the importance of management accounting in upravlinnni modern enterprise, its functionality in managerial concepts. The article is devoted to the consideration of some outstanding scientists approaches to the interpretation and purpose of “managerial reporting” notion. The expediency of the proposed “intra-corporate managerial reporting” term using is grounded, in order to reflect the objective of its further using with a view to put into practice the carried information and meaning. The classification of managerial reporting presented by some outstanding scientists is considered also. Grounded appropriate format of the information provided internal management reporting required to support effective management decisions. Presented arguments and outlines some approaches by which management reporting structure of intra corporate can be modified and developed by extending one of its components, including the one which allows us to differentiate intra management reporting and responsibility centers and other segments of the industry, products, structural units and so on. The author’s position on structuring and determination of “intra-corporate managerial reporting” composition and also its place in the information management system is substantiatly presented.
Modern interpretation, composition and features of enterprise managerial reporting formation
Keywords: управлінська звітність; внутрішньокорпоративна управлінська звітність; класифікація; склад; managerial reporting; intra-corporate managerial reporting; classification; composition